Metabolismen Nahrungsmittel als Kunstmaterial - Augart, Isabella; Jessen, Ina (Hamburg University Press, 2019)
Located at the link between man and the nature that surrounds him, food overlaps in the cycle of production, preparation, consumption and excretion of biological necessity, cultural technique and cultural transformation. Against the background of cultural-scientific contexts, food is examined as an "art material", as a material and motif of art, and the material "metabolism" that can be grasped in it between cultural valuations and processes of decay. The anthology brings together questions, discussions and perspectives from the two-day conference "Metabolisms. Food in Art" at the Warburg House and the Dieter Roth Museum Hamburg in November 2017.